Business Ethics: Practical Proposals for Organisations - McDonald, Gael (Journal of business ethics, 1999)
A review of ethical literature demonstrates that the material presented to date is largely based upon theoretical and empirical research. While this information has contributory value, the information produced is largely observational rather than practical. Managers are anxious to receive assistance with the mechanisms by which ethics can be integrated into their organisations. Utilising the recent experience of the author with a large utility company in Asia committed to developing an ethical programme to enhance ethical awareness in their organisation, this paper intends to review current systems and procedures available to managers for integrating ethics into business. In addition to reviewing mechanisms for promoting an ethical climate, where appropriate, reference will be made to prior research and specific organisations where these practices have been used successfully. The paper concludes with a set of summary recommendations for managers embarking on the introduction of an ethical programme to their organisation.